Adult hippocampal neurogenesis impairment at preplaque stage in a transgenic rat model of Alzheimer like amyloid pathology - Galeano, Pablo (2019)
The contribution of adult hippocampal neurogenesis (AHN) impairment on cognitive decline in early Alzheimer disease (AD) remains poorly understood. This can be ascribed to the technical difficulties to measure AHN in postmortem brains and patients. Furthermore, most animal models of AD exhibit an aggressive neuropathology at early age and harbor gene mutations and express transgenes that disrupts AHN by pathways not directly involved in AD pathology. To overcome some of these limitations, we studied AHN at preplaque stage (6 month old) in hemizygous (Tg+/-) and homozygous (Tg+/+) McGill-R-Thy1-APP transgenic rats. This model exhibits a much less aggressive neuropathology that nevertheless is associated with a marked cognitive impairment from early age. Our results revealed that Tg+/+ rats showed a reduced number of PCNA+ cells, DCX+ immature neurons and BrdU+/NeuN+ colabed neurons in dorsal and ventral dentate gyrus. Moreover, dendritic arborization was less developed. AHN was not impaired in Tg+/- rats, although dendritic arborization was slightly decreased. On the other hand, both hemizygous and homozygous rats exhibited spatial memory impairments in the Morris water maze. These results suggest that 1) AHN is dysregulated from the preplaque stage in homozygous rats, 2) AHN impairment is dependent on APP transgene copy numbers since hemizygous rats did not show it, 3) Dysregulation of AHN is not directly associated with spatial memory impairments since hemizygous rats exhibited spared neurogenesis despite showing spatial memory deficits. Funding: International Society for Neurochemistry CAEN Grant and Andalucia TECH-ICE (PG), and PICT-2015-0285 (LM).